YjbH-Enhanced Proteolysis of Spx by ClpXP in Bacillus subtilis Is Inhibited by the Small Protein YirB (YuzO) - Kommineni, Sushma (American Society for Microbiology, 2011)
The Spx protein of Bacillus subtilis is a global regulator of the oxidative stress response. Spx concentration is controlled at the level of proteolysis by the ATP-dependent protease ClpXP and a substrate-binding protein, YjbH, which interacts with Spx. A yeast two-hybrid screen was carried out using yjbH as bait to uncover additional substrates or regulators of YjbH activity. Of the several genes identified in the screen, one encoded a small protein, YirB (YuzO), which elevated Spx concentration and activity in vivo when overproduced from an isopropyl-β-d-thiogalactopyranoside (IPTG)-inducible yirB construct. Pulldown experiments using extracts of B. subtilis cells producing a His-tagged YirB showed that native YjbH interacts with YirB in B. subtilis. Pulldown experiments using affinity-tagged Spx showed that YirB inhibited YjbH interaction with Spx. In vitro, YjbH-mediated proteolysis of Spx by ClpXP was inhibited by YirB. The activity of YirB is similar to that of the antiadaptor proteins that were previously shown to reduce proteolysis of a specific ClpXP substrate by interacting with a substrate-binding protein.